LAS: A combination of the analytic signal amplitude and the generalised logistic function as a novel edge enhancement of magnetic data - PHAM, Luan Thanh; OKSUM, Erdinc; DO, Thanh Duc; LE-HUY, Minh; VU, Minh Duc; NGUYEN, Vinh Duc (Contributions to Geophysics and Geodesy, 2019)
In the evaluation of magnetic field data, edge enhancement and detectiontechniques are important treatments for the interpretation of geological structures. Ingeneral geological sense, contiguity of deep and shallow magnetic sources leads to weakand intense anomalies that complicates the interpretation to disclose adjacent anomaloussources. Many of the existing filters for edge detection in magnetics mostly have the disadvantagethat they require a reduction to pole transformation as the pre-process of thedata or they cannot balance weak and intense anomalies and therefore fail in detectingedges of deep and shallow sources simultaneously. This study presents an improved edgedetection filter LAS (logistic function of the analytical signal), based on the generalisedlogistic function configured by the ratio of derivatives of the analytical signal. This novelapproach has the capability of reducing the dependence on the direction of the magnetizationand also balancing anomalies of sources at different levels of depth. The feasibility ofthe method is examined on both theoretical and real data cases comparatively with someother methods that utilize the analytical signal in their basis. In comparison, the resultsdemonstrate that the LAS method provides more accurate estimation of edge localization.